Seasonal Effects on Nutrient and Bioactive Element Distributions in the Surface Sediments of Calabar River, Calabar, South-East Nigeria - Abasiekong, Beauty Omayeli; Osabor, Vincent Ndem (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The contamination of metals (Fe, Zn, Ni, Mn, Mg, Cd, Cr and Pb) and abundance of nutrients (NO3-, NO2-, NH4+, PO43-, TN and TP) in the surface sediment of Calabar river during wet and dry seasons of the year was studied to evaluate their distribution, ecological risk and possible resource limitation within the ecosystem. The result obtained showed that average concentration of nutrient increased in the order PO43-(0.61) < TP (1.99) < NO2-(2.11) < NH4+(5.74) < NO3-(33.10) < TN (48.42) μM while that of metals were Cd (0.18) < Cr (1.61) < Mn (1.80) < Zn (3.42) < Pb (5.33) < Ni (7.18) < Mg (21.64) < Fe (38.44)mg/kg for wet season and PO43-(0.57) < TP (1.76) < NO2-(2.49) < NH4+(4.996) < NO3-(31.24) < TN (47.10)μM and metals, Cd (0.28) < Cr (0.899) < Mn (3.588) < Zn (4.60) < Pb (4.60) < Ni (7.73) < Mg (17.12) < Fe (31.96)mg/kg for dry season. Considering the sediment quality guideline classification, ERL/ERM, TEL/PEL and LEL/SEL, these metals pose no environmental risk. Also, several standard indices: EF, CF, MPL, Cd, MCd, RI and PERI were used to evaluate the sediment pollution status and its ecological risk and the result showed no contamination and low environmental risk. The Redfield ratio of NO3-: PO43- and TN: TP for these study sites were within 16: 1 and 30: 1 during the dry season. However, during the wet season NO3-: PO43- got very high to about 54: 1. This is an indication of PO43- limitation and excess NO3-. Finally,statistical analysis including Pearsonrank order correlation ɤ, Spearman correlation, ANOVA and Turkey HSD multiple comparison were applied to evaluate the sources and the significance in their relationship at probabilities levels of p< 0.1, p<0.05 and p<0.01.